1997
DOI: 10.1046/j.1365-2567.1997.d01-2308.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation in vitro of human natural cytotoxicity, lymphocyte proliferative response to mitogens and cytokine production by essential fatty acids

Abstract: SUMMARYEssential fatty acids ( EFA) have been shown in animal studies to have a differential effect on various aspects of immune reactivity. However, there have been few studies in humans. Therefore, we elected to investigate the effects of a variety of EFA [gamma-linolenic acid (GLA), eicosapentaenoic acid ( EPA) and docosahexaenoic acid (DHA)] in vitro on human blood lymphocyte reactivity, cytokine secretion and natural cytotoxicity. The proliferative response to polyclonal mitogens (phytohaemagglutinin, pok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 35 publications
4
53
0
Order By: Relevance
“…Specifically, in vitro studies have shown that EPA and DHA suppress IL-6 production by human endothelial cells (Khalfoun et al, 1997). EPA and DHA have been reported to suppress the in vitro production of IL-1, IL-2, IL-6, TNF-a and INF-g by human lymphocytes (Purasiri et al, 1997). Human studies have indicated that dietary supplementation with EPA and DHA results in suppression of IL-1, IL-2, IL-6 and TNF-a production by monocytes (Calder, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in vitro studies have shown that EPA and DHA suppress IL-6 production by human endothelial cells (Khalfoun et al, 1997). EPA and DHA have been reported to suppress the in vitro production of IL-1, IL-2, IL-6, TNF-a and INF-g by human lymphocytes (Purasiri et al, 1997). Human studies have indicated that dietary supplementation with EPA and DHA results in suppression of IL-1, IL-2, IL-6 and TNF-a production by monocytes (Calder, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Gamma-linolenic acid reduces IL-1beta secretion by monocytes (22). Other authors (23,24) have found that omega-6 PUFAs generally raise IL-1 production and that omega-3 PUFAs have the opposite effect.…”
Section: Production Of Cytokines and Other Cell Mediators Antigen Prmentioning
confidence: 96%
“…On the other hand, human neutrophils treated with omega-3 fatty acids show decreased production of IFN-gamma (24).…”
Section: Production Of Cytokines and Other Cell Mediators Antigen Prmentioning
confidence: 97%
See 2 more Smart Citations